A Survey of Air Quality Index and Quantification of Cardiovascular Mortality due to Exposure to Particulate Matter Smaller than 2.5 Micron in Boukan in 2015 - Majid Kermani (Muhandisī-i Bihdāsht-i Muḥīṭ, 2017)
Background: The influx of dust to the North West of Iran during past decade has become a serious threat to the health and economy of the region and has created many human and financial damages. So, the aim of this study is to quantifying cardiovascular mortality resulted from exposure to Particulate matter smaller than 2.5 micron in Bokan in 2015 using Air Q software. Methods: This descriptive-analytic study was carried out in Bokan. The measurement of PM2.5 Concentration was done using MP101M Device around the clock in 2015, which yielded data collected for 321 days. Meteorological data, including wind speed and direction, and relative humidity were obtained from office of Meteorology. The software, using data processed with Excel, calculated Relative Risk, baseline incidence and attributable proportion and showed the output in terms of mortality. Results: Based on the statistics of air pollution monitoring station, maximum hourly PM2.5 concentration was 400.52 micrograms per cubic meter and the number of total mortality attributed to exposure to PM2.5 in 2015 was 50 cases. Conclusion: The number of total mortality attributed to exposure to PM2.5 resulted from the influx of dust, necessitates immediate action to solve the dust problem, as well as dissemination of all facilities and information through public media in order to educate people about how to deal with this dangerous phenomenon.